Socio-Cultural and Individual Determinants of Psychoactive Substance Used among College Students: A Case Study in North Kashmir, India - Malla, Manzoor Ahmad (Selangor Humaniora Review, 2021)
The epidemic of substances among college students has caused great concern in recent decades. However, most research studies have focused on the biological and psychological aspects of drug addiction. Few researchers have studied the socio-cultural and personal variables that influence substance abuse, resulting in limited findings. The present study addresses the socio-cultural and individual determinants which influence the use of psychoactive substances among college students in the North Kashmir region of India. The present study was conducted in the six government degree college located in the North Kashmir region of India. 320 respondents (college students) were selected by snowball sampling technique, and their demographic information and type of substance use were assessed by a standard questionnaire. The study results show that most of the respondents are males from the age group of 20-22 years, from nuclear families and urban backgrounds. A high prevalence of psychoactive substance abuse was found among the students enrolled in the Bachelor of Arts course. Psychoactive substances such as spasmoproxyvon tablets, opium, charas, and codeine phosphate are the main substances. Socio-cultural factors like peer group influence, easy availability, family problems, as well as personal determinants like curiosity, seeking for pleasure, academic stress, and failure in love affairs are the main causes of substance abuse. Therefore, the results of this study can be utilized for understanding the cause of the problem, prevention, and treatment. Substance use was more prevalent among male students with arts academic backgrounds. It suggests that we require goal-directed programs to regulate and minimize the extent of substance use, enhance students’ awareness, and increase students understanding of the negative consequences of substance use in their entry.